2021
DOI: 10.1016/j.arth.2021.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of KOOS Scores of Middle-Aged Patients Undergoing Total Knee Arthroplasty to the General Dutch Population Using KOOS Percentile Curves: The LOAS Study

Abstract: Background: We aimed to investigate the application of the Knee Injury and Osteoarthritis Outcome Score (KOOS) percentile curves, using preoperative and postoperative data of patients with knee osteoarthritis undergoing total knee arthroplasty (TKA). Methods: We used Longitudinal Leiden Orthopedics Outcomes of Osteo-Arthritis study data of patients between 45 and 65 years and undergoing primary TKA. KOOS scores (0-100) were obtained preoperatively and 6, 12, and 24 months after TKA. Preoperative knee radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(35 reference statements)
3
0
0
Order By: Relevance
“…The results of our study demonstrated a significant improvement in the Oxford Knee Score, all KOOS sub-scores, and the KSS satisfaction sub-score at 6 months post-surgery. The significant improvements were similar to those previously reported after in-person interventions in Belgium and The Netherlands [32][33][34], and the population studied was representative of the registry in terms of demographics [35]. The absence of direct comparison with standard protocols in our study limits further conclusions, but the results of our study confirmed previous reports in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…The results of our study demonstrated a significant improvement in the Oxford Knee Score, all KOOS sub-scores, and the KSS satisfaction sub-score at 6 months post-surgery. The significant improvements were similar to those previously reported after in-person interventions in Belgium and The Netherlands [32][33][34], and the population studied was representative of the registry in terms of demographics [35]. The absence of direct comparison with standard protocols in our study limits further conclusions, but the results of our study confirmed previous reports in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Total joint arthroplasty reportedly improves HRQOL after surgery. 7,29) We observed that the preoperative KOOS scores in our study were similar to 30,31) or better than 32) those reported in previous studies. In studies with worse preoperative KOOS scores, the patients were younger (mean age, approximately 60 years) at the time of TKA.…”
Section: Discussionsupporting
confidence: 89%
“…The observed differences may be explained by differences in lifestyle and physical activities associated with age and anxiety about the future. In a large prospective cohort study, 32) the KOOS scores at 12 months post-TKA were similar to the re-sults of the current study. However, in that study, the KOOS scores at 24 months post-TKA remained unchanged from those at 12 months post-TKA.…”
Section: Discussionsupporting
confidence: 87%